2013
DOI: 10.15193/zntj/2013/90/052-063
|View full text |Cite
|
Sign up to set email alerts
|

Quality Profile of Meat From Different Carcass Cuts of Roe Deer (Capreolus Capreolus L.) Bucks Hunter-Harvested in North-East and South-East Poland

Abstract:  CHARAKTERYSTYKA JAKOŚCI MIĘSA Z RÓŻNYCH ELEMENTÓW TUSZY KOZŁÓW SARNY EUROPEJSKIEJ (CAPREOLUS CAPREOLUS L.) ODSTRZELONYCH W PÓŁNOCNO-WSCHODNIEJ I POŁUDNIOWO-WSCHODNIEJ POLSCES t r e s z c z e n i e Celem przeprowadzonych badań było porównanie jakości mięsa pochodzącego z różnych elementów tuszy kozłów sarny europejskiej (Capreolus capreolus L.) pozyskanych przez myśliwych w lasach pół-nocno-wschodniej (10 szt.) i południowo-wschodniej (10 szt.) Polski. Badaniami objęto cztery podstawowe elementy tuszy kozłów,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…Analysing the influence of the animal's sex on the content of protein and fat in roe deer meat, Daszkiewicz et al [44] found more nutrients in the meat of does (22.79% and 1.46%) than of bucks (21.84% and 0.83%). Irrespective of where roe deer bucks were culled, Daszkiewicz et al [45] noted a higher water-to-protein ratio than in our own study. In turn, the W/P ratio in red deer meat was close to values reported by Daszkiewicz et al [5].…”
Section: Discussioncontrasting
confidence: 59%
“…Analysing the influence of the animal's sex on the content of protein and fat in roe deer meat, Daszkiewicz et al [44] found more nutrients in the meat of does (22.79% and 1.46%) than of bucks (21.84% and 0.83%). Irrespective of where roe deer bucks were culled, Daszkiewicz et al [45] noted a higher water-to-protein ratio than in our own study. In turn, the W/P ratio in red deer meat was close to values reported by Daszkiewicz et al [5].…”
Section: Discussioncontrasting
confidence: 59%